Beneficiation of Tailings from Primary Tin Processing from Iron Ore Mines at PT Timah Tbk in PPBT Tanjung Ular - Setiawan, Agris; Manalu, Naomi B; Setyani , Atik; Wahyuningsih, Tri; Putri, Adinda; Andreana, Mellyna (Journal of Metallurgical Engineering and Processing Technology, 2025)
The tailings produced from the previous processing are known to still contain valuable minerals such as cassiterite (SnO2), as well as associated minerals such as Fe, ilmenite, and zircon. Therefore, a beneficiation process is needed to optimize tin recovery and minimize the loss of valuable minerals. The beneficiation process includes sampling, sample reduction, grinding using a rod mill, and separation of valuable minerals using a shaking table and wet magnetic separator, as well as X-ray fluorescence (XRF) analysis. The XRF results of primary tin concentrate beneficiation using a shaking table increased the Sn content from 0.736-1.259% to 20-18.99% with a recovery of 1.779-7.456%. Magnetic separation of 40 kg of feed produced magnetic fractions of 5.7 kg and 18 kg, with Fe grades of 8.96–8.99% and Sn up to 4.90%. The grade increase was achieved, but Fe separation was still not optimal because some magnetic minerals were carried over to the non-magnetic fraction.